An Assessment Approach to Innovations in Existing Routes and Novel Drug Delivery System - Gupta, Anshu; Sharma, Diwanshu (Issues and Developments in Medicine and Medical Research Vol. 8, 2022)
New drug delivery systems (NDDS) are developed for improvement in efficacy of the drugs, provide maximum benefit to the patient and to minimize the adverse drug reactions. For local anaesthetics (LAs), the development of new effective delivery systems modulate the release rate, extend their anaesthetic effect , and helps to enhance their localisation as desired. The various routes of local anaesthetic delivery (epidural, peripheral, wound catheters, intra-nasal, intra- vesical, intra-articular, intra-osseous) are under innovation these days. Different methods such as include iontophoresis, electroporation, sonophoresis, and magnetophoresis are being used to enhance local anaesthetic permeation. Adjuvants are added to potentiate drug effects. The use of different delivery systems should help to keep the LA at the target site for longer periods prolonging the anesthetic or analgesic effect with an extended range of agents. New drug delivery systems for local anaesthesia provide better analgesia and anaesthesia by altering the sensory component mainly. Efficacy and tolerability of drugs is improved by these novel methods.